2023
DOI: 10.3390/cancers15072149
|View full text |Cite
|
Sign up to set email alerts
|

Risk Classification of Bladder Cancer by Gene Expression and Molecular Subtype

Abstract: This study evaluated a panel including the molecular taxonomy subtype and the expression of 27 genes as a diagnostic tool to stratify bladder cancer patients at risk of aggressive behavior, using a well-characterized series of non-muscle invasive bladder cancer (NMIBC) as well as muscle-invasive bladder cancer (MIBC). The study was conducted using the novel NanoString nCounter gene expression analysis. This technology allowed us to identify the molecular subtype and to analyze the gene expression of 27 bladder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 89 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…By contrast, MIBCs require the inactivation of one or more tumor suppressor genes, such as TP53 , RB1 , and PTEN , and tumor development is preceded by the appearance of flat urothelial dysplasia and carcinoma in situ; interestingly, these lesions share molecular features with high grade and invasive bladder carcinomas (fig 3). 316182039…”
Section: Pathophysiology and Molecular Stepsmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, MIBCs require the inactivation of one or more tumor suppressor genes, such as TP53 , RB1 , and PTEN , and tumor development is preceded by the appearance of flat urothelial dysplasia and carcinoma in situ; interestingly, these lesions share molecular features with high grade and invasive bladder carcinomas (fig 3). 316182039…”
Section: Pathophysiology and Molecular Stepsmentioning
confidence: 99%
“…The CDKN2A locus (9p21) encodes p16 and p14ARF, which are negative regulators of the RB pathway and p53 pathway, respectively. Chromosome 9 loss also implicates TSC1 , a tumor suppressor that regulates mammalian target of rapamycin (mTOR) signaling 35101218212227282940414243. Additional deletions of chromosome arms 10q, 11p, 11q, 17p, 18q, 19p, and 19q have been described in up to 20% of cases.…”
Section: Pathophysiology and Molecular Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ta, a papillary tumor, grows into the hollow area of the bladder with finger-like projections but does not spread to the connective tissue or muscle tissue of the bladder wall [38]. Cancers in the Ta and CIS stages account for 70% and 20% of all NMIBC, respectively [39]. Tumors in stage T1 spread into the connective tissue layer (lamina propria) under the lining layer of the bladder, but do not spread into the muscle layer.…”
Section: Stages Of Bladder Cancermentioning
confidence: 99%
“…However, several previous studies reported that bladder cancer shows clinical variations depending on its histological type [4,11,[23][24][25]. Furthermore, a recent study analyzing gene expression in bladder cancer showed that UC has different gene expression patterns, depending on the molecular or histological subtype [26]. Some studies have reported differences in the molecular characteristics of UC depending on the primary tumor site [27][28][29].…”
Section: Introductionmentioning
confidence: 99%